Not for you? Ethical implications of archiving zines. (1st June 2019) - Fife, Kirsty
The archival value of zines (self-published pamphlets often produced by radical and marginalized communities) as historical records has been well documented in academic research. Red Chidgey refers to zines as 'sources of advocacy and empowerment for those who make them, an attempt to bear witness to their own lives'. As evidence of networks, cultures, linguistics and experiences of marginalized individuals and communities, zines often exist as the only representation of ephemeral and otherwise undocumented spaces, which makes them incredibly valuable as the primary source material.Following the establishment of large zine collections at heritage spaces including the Women's Library, British Library, Wellcome Library and Tate, zines are now regularly collected and used in programming at heritage organizations. But what does it mean to archive and make use of zines – particularly those created by marginalized makers and communities – in an institutional heritage context? This article considers the ethical implications of archiving zine practice and cultures – anti-institutional in its nature – in institutional spaces. Through a case study analysis of the community-led archive project Queer Zine Archive Project, I argue that, if zines are archived, it is imperative that archive workers are critically thinking about and incorporating the originating politics of zine culture into protocols for cataloguing, access, interpretation and use of these materials.